Fracture resistance of teeth restored with packable and hybrid composites - Ghavam M; Ataee M; Fallahzade F (Tehran University of Medical Sciences, 2006)
Background and Aim: With recent introduction of packable composites, it is claimed that they apply less stress on tooth structure because of reduced polymerization shrinkage, and similarity of coefficient of thermal expansion to tooth structure. However, the high viscosity may in turn cause less adaptation, so it is not clearly known whether these materials strengthen tooth structure or not. The aim of this study was to evaluate fracture resistance of maxillary premolars, receiving hybrid or packable composite restorations with different methods of application and curing. Materials and Methods: In this experimental study, seventy five intact premolars were randomly assigned to five groups of 15 teeth each. One group was maintained intact as the control group. Similar MOD cavities were prepared in the other teeth. The teeth in group two were restored with Spectrum in incremental layers and light cured with 500 mw/cm2 intensity. The third group were filled with Surefil and cured with light intensity of 500 mw/cm2. The groups four and five were restored with Surefil in bulk technique with two different modes: 500 mw/cm2 intensity and a ramp mode (100-900 mw/cm2) respectively. After thermocycling, force to fracture was assessed and degree of conversion (DC) at the bottom of cavities was evaluated for different modes and methods. The curing and placement methods in groups tested for DC (A to D) were the same as fracture resistance groups (2 to 5). Data were analyzed using one way ANOVA and Tukey HSD tests with p<0.05 as the limit of significance. Results: All the restored groups showed significantly less fracture resistance than the control group, but had no significant difference among themselves. DC of Spectrum was higher than Surefil. Bulk method with 500 mw/cm2 light intensity, significantly decreased DC. DC in bulk method with high light intensity was not significantly different from incremental method with 500 mw/cm2 light intensity. Conclusion: Placement techniques, light intensity and type of composite had no influence on the fracture resistance. The use of packable composite with bulk technique and 500 mw/cm2 intensity or less is not recommended in 4 mm depth cavities due to insufficient DC.